Influence of Foliar Application of Nanoparticles on Low Temperature Resistance of Rice Seedlings - Shafi Ullah; Muhammad Ikram; Jian Xiao; Atika Khan; Ismail Din; Jianliang Huang (Plants)
Chilling stress, a common abiotic factor, adversely affects the growth and biomass of rice seedlings during the early stages, ultimately reducing the yield. Effective strategies to mitigate these negative impacts are essential for improving rice productivity. The application of nanotechnology in agriculture, particularly nanoparticles (NPs), has shown a promising effect in alleviating chilling stress in plants. This study evaluates the effects of various nanoparticles, ZnO (0, 50, 100, and 200 mg/L), Fe2O3 (0, 50, 75, and 100 mg/L), TiO2 (0, 50, 75, and 100 mg/L), and CeO2 (0, 50, 75, and 100 mg/L) on the chilling resistance with one control (a water spray) under a normal temperature. Four rice cultivars: LLY-7108 and XZX-6 (Low-temperature-tolerant), and LLY-32 and ZJZ-17 (Low-temperature-susceptible) were tested in this experiment. Rice seedlings were subjected to low temperature conditions (12 h light 14 °C/12 h dark, at 10 °C) for five days, followed by seven days of recovery. The results of this study demonstrate that NPs significantly enhanced seedling height fresh/dry weight and root length compared to untreated controls under chilling stress. NP treatment also reduced the reactive oxygen species (ROS), malondialdehyde (MDA), and proline content, while enhancing superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) activities, thereby mitigating oxidative damage. The four rice varieties exhibited clear signs of rapid growth recovery and positive physiological changes due to NPs’ application. Among the tested cultivars, LLY-7108 showed the most substantial recovery and physiological responses, while ZJZ-17 exhibited the least. The findings of this study indicate that the foliar application of ZnO (100 mg/L), Fe2O3 (50 mg/L), TiO2 (50 mg/L), and CeO2 (75 mg/L) NPs effectively mitigates chilling stress in rice seedlings, likely by enhancing the antioxidant enzymatic activity while reducing the oxidative damage. This study highlights the potential of NPs as effective agents in reducing the adverse effects of chilling stress on rice.